An analysis of surgically treated cutaneous malignancies in central India - Jain, Amar; Desai, Sanjay; Ahmad, Zeeshanuddin; Agrawal, Deepak; Mehta, Nikhil (International Journal of Research in Medical Sciences, 2018)
Background: Cutaneous malignancies constitute one of the most common human malignancies. Annually, more than 400,000 people are diagnosed to have skin cancer. The skin cancers are classified into melanomas and non-melanoma skin cancers (NMSC). In India, skin cancers constitute about 1-2% of all the diagnosed cancers. The present study was undertaken on 41 patients presented to tertiary health centre to measure the frequency of cutaneous malignancies in our set up, analyse the demographic profile of the patients, assess the associated morbidity and mortality, formulate the treatment protocols and collect actionable evidence base for evolving useful strategies to address this emerging public health issue. Methods: Present study was carried out in the Department of surgical oncology, Sri Aurobindo Institute of Medical Sciences (SAIMS), Central India during the period from Jan 2015 to Dec 2017. The patients included in this study fulfilled the inclusion criteria which was first who presented with cutaneous malignancy confirmed by histopathology and surgical intervention. Results: Out of a total of 41 patients with various cutaneous malignancies, 53.7% (n=22) were males while 46.3 % (n=19) were females. The mean age was 53.92 years. There were 24 cases of SCC, 4 cases of BCC, 5 cases of malignant melanoma, two cases of malignant fibrous histiocytoma, two cases of sebaceous and one case each of dermatofibrosarcoma protuberans, epithelioma, capillary haemangioma and poorly differentiated carcinoma respectively. Face was the most frequent site of involvement (n=17), followed by trunk (n=6), scalp (n=5), lower limb (n=5), genital (n=4), upper limb (n=3) and neck (n=1). Conclusions: Cutaneous malignancies are not uncommon in our set up. In our set up, SCC constitutes the leading type. Painless skin lesion of a relatively long duration is the usual presenting feature. There is intense need of mass awareness and to impart knowledge about the medical and socioeconomic implications of this emerging health issue. This will not only help to prevent the avoidable causes but also prompt early medical consultation in case an individual develops such skin lesions.